A Robust Porphyrin‐Stabilized Triplet Carbon Diradical. (24th February 2021) - Wang, Kaisheng; Liu, Pingting; Zhang, Fenni; Xu, Ling; Zhou, Mingbo; Nakai, Akito; Kato, Kenichi; Furukawa, Ko; Tanaka, Takayuki; Osuka, Atsuhiro; Song, Jianxin
Abstract: The synthesis of robust high‐spin carbon radicals is an important topic in organic chemistry. Toward this end, several porphyrin‐stabilized radicals have been systematically explored. A singly naphthalene‐fused porphyrin radical was synthesized by a reaction sequence consisting of a Suzuki–Miyaura coupling of β‐borylated porphyrin with 2‐bromobenzaldehyde, addition of mesityl Grignard reagent, intramolecular Friedel–Crafts alkylation, and final oxidation with DDQ or t BuOK/O2 . This strategy was also used to synthesize doubly naphthalene‐fused porphyrins and syn ‐ and anti ‐fused‐anthracene‐bridged porphyrin dimers. While singly naphthalene‐fused porphyrin radical has been shown to be a stable monoradical, doubly naphthalene‐fused porphyrins and anti ‐fused‐anthracene‐bridged porphyrin dimers have been shown to be closed‐shell molecules. Finally, the syn ‐dimer was characterized as a surprisingly stable radical ( t 1/2 =28 days under ambient air and at 80 °C) that is storable for more than several months, despite its high‐spin triplet ground‐state carbon diradical. Abstract : Naphthalene/anthracene‐fused porphyrins were synthesized by a Suzuki–Miyaura coupling and subsequent intramolecular Friedel–Crafts alkylation and oxidation. The structures of 3Ni, 6Ni, 9Ni, 11Ni, and 13Ni have been confirmed by X‐ray crystallographic analysis. 11Ni is characterized as a surprisingly stable radical ( t 1/2 =28 days under ambient air and at 80 °C) that is storable for more than several months, despite its high‐spin triplet ground‐state carbon diradical.